Assessment of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and mean platelet volume in patients with diabetic retinopathy - Trisha Ghosh; Sanjay Kumar Daulat Thakur; Premangshu Ghosh; Trina Sengupta (Journal of Clinical Ophthalmology and Research)
Objective: The objective of this study was to assess the role of inflammation in the pathogenesis of diabetic retinopathy (DR) using the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV) and to compare these parameter levels between DR and non-DR (NDR) subjects. Materials and Methods: A cross-sectional study was conducted among 60 patients with a definite diagnosis of type 2 diabetes mellitus attending the ophthalmology outpatient department of a tertiary care hospital. We obtained blood samples from all individuals who participated in the study to investigate these parameters. Results: Sixty subjects were included in this study: 30 in the DR group and 30 in the NDR group. The mean NLR, PLR, and MPV levels were higher in DR subjects than in NDR subjects (NLR: 2.49 ± 0.82 in DR group vs. 1.94 ± 0.75 in NDR group, P = 0.003; PLR: 114.82 ± 5.08 in DR group vs. 104.5 ± 6.73 in NDR group, P = 0.01; and MPV: 11.08 ± 1.28 in DR group vs. 9.92 ± 1.63 in NDR group, P = 0.003). Conclusion: The higher NLR, PLR, and MPV levels found in patients with DR may indicate that subclinical systemic inflammation may be associated with DR. Understanding the potential association between NLR, PLR, MPV, and DR holds promise in providing valuable clinical information for the early detection and effective management of DR. Moreover, unraveling the underlying mechanisms linking these ratios with the pathophysiology of DR could contribute to the development of targeted screening and therapeutic interventions.